2023
DOI: 10.1200/jco.22.02221
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of Axitinib and Avelumab in Patients With Recurrent/Metastatic Adenoid Cystic Carcinoma

Abstract: PURPOSE We conducted a phase II trial evaluating the efficacy of VEGFR inhibitor axitinib and PD-L1 inhibitor avelumab in patients with recurrent/metastatic adenoid cystic carcinoma (R/M ACC). PATIENTS AND METHODS Eligible patients had R/M ACC with progression within 6 months before enrollment. Treatment consisted of axitinib and avelumab. The primary end point was objective response rate (ORR) per RECIST 1.1; secondary end points included progression-free survival (PFS), overall survival (OS), and toxicity. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Given the difficulty in distinguishing between ACC disease stability and drug-induced stability, the results of this RCT are strong evidence that axitinib delays ACC progression . Of note, while our meta-analysis looked exclusively at VEGFR inhibitors as single agent, a 2023 trial of combination of axitinib plus the programmed death-ligand 1 inhibitor avelumab showed positive outcomes, garnering inclusion in the updated NCCN guidelines…”
Section: Discussionmentioning
confidence: 90%
“…Given the difficulty in distinguishing between ACC disease stability and drug-induced stability, the results of this RCT are strong evidence that axitinib delays ACC progression . Of note, while our meta-analysis looked exclusively at VEGFR inhibitors as single agent, a 2023 trial of combination of axitinib plus the programmed death-ligand 1 inhibitor avelumab showed positive outcomes, garnering inclusion in the updated NCCN guidelines…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, cylindromas with malignant behavior are referred to as adenoid cystic carcinoma (ACC) to accurately describe their pathological features and clinical manifestations. Today, ACC is the most common term for the lesion [ 21 ]. As one of the most common epithelial malignant tumors of the salivary glands, ACC is highly invasive and neurophilic, easily infiltrates blood vessels, and rarely spreads to the lymph nodes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a recent study showed that MYB is essential for the development of precursors of exhausted T cells, and the response to PD-1 checkpoint inhibition depends on MYB expression [35], which is consistent with our results. Furthermore, very recently, the addition of the PD-L1 inhibitor avelumab to axitinib has been shown to be beneficial in ACC of the head and neck [36], leading to its inclusion as a therapeutic option for ACC in the National Comprehensive Cancer Network guidelines.…”
Section: Discussionmentioning
confidence: 99%